Incumbent Performance Dissatisfaction Influences Blank-Box Voting in the 2024 Gresik Election - Shine Kurdiati Miare; Fatkah Ainurrofiah; Budi Santoso; Mochamad Arif Affandi (PT Pro Panoramic Solution, 2026)
The high proportion of blank votes in the 2024 regional election in Gresik Regency reflects an important phenomenon in local democratic participation, particularly in uncontested elections. Despite the increasing occurrence of blank voting in Indonesia, empirical evidence explaining how public dissatisfaction with incumbent performance influences this behavior remains limited. This study aims to examine the effect of public dissatisfaction with incumbent performance on the propensity to vote for the blank box. A quantitative research design was employed using data from 150 respondents selected through quota sampling from five sub districts Sidayu, Bungah, Manyar, Ujungpangkah, and Kebomas which recorded the highest proportion of blank votes in the election. Data were collected through structured Likert-scale questionnaires and analyzed using multinomial logistic regression. The findings indicate that the model demonstrates a good fit, with a significant Omnibus Test (p < 0.001) and Pearson and Deviance statistics exceeding 0.05. Public dissatisfaction has a statistically significant effect on the likelihood of voting for the blank box (Exp(B) = 1.687, p < 0.001). These findings extend rational choice theory by demonstrating that, in uncontested local elections, blank voting represents a rational mechanism of electoral accountability rather than merely political apathy. This study provides empirical evidence that public evaluations of incumbent performance constitute a significant determinant of blank-box voting in single-candidate local elections, thereby enriching the understanding of electoral behavior in uncontested democratic contests. The study contributes to the literature on electoral behavior by highlighting public performance evaluation as an important determinant of blank voting in local elections.